(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
This article study comprehensively analyzes the impact of the transformation of the electronic reporting system in the Republic of Uzbekistan on the economic efficiency of business entities. The study examines the reforms implemented in the period 2023–2026, in particular, measures implemented within the framework of the "Digital Uzbekistan - 2030" strategy, factors for optimizing reporting types and reducing transaction costs.